A framework for library space and the satisfaction of academic library users need / Nur Aina Aliaa Ahmad Latfi. - Ahmad Latfi x, Nur Aina Aliaa (Universiti Teknologi MARA Cawangan Selangor, 2016)
In the recent year academic library nowadays are towards focusing in designing the library space as to increase back the number of gate count and circulation activities. Knowing the importance of various spaces that can meet the need of users, have made this initiative becomes the common goal of many academic libraries. Consideration on the entire planning are really needed in order to support the learning and teaching activities as to meet their users need or behavior of each type of spaces that are required. To know the need of space that are required by many academic users four type of space are been discuss in this paper in order to well known about the major factor that affect the use of spaces and also their need towards each spaces. Basically, the purpose of this paper is to propose the framework on the four types of spaces that focus on the collaboration space, individual space, interaction space and the community space which it can give big impact on the satisfaction of users need. Inside this paper also there is a section on the literature review that gives information to the reader regarding the library space itself. The previous study model and framework also been discuss in this paper in order to knows the types of space that regularly been required by the academic library user. Follow by that, the framework are been discuss in detail which focus on user's satisfaction and the four types of space.